2D Perovskites: Unraveling the Crystallization Kinetics of 2D Perovskites with Sandwich‐Type Structure for High‐Performance Photovoltaics (Adv. Mater. 36/2020). Issue 36 (8th September 2020) - Song, Jingnan; Zhou, Guanqing; Chen, Wei; Zhang, Quanzeng; Ali, Jazib; Hu, Qin; Wang, Jing; Wang, Cheng; Feng, Wei; Djurišić, Aleksandra B.; Zhu, Haiming; Zhang, Yongming; et al.
Abstract : In article number 2002784, Qin Hu, Haiming Zhu, Feng Liu, and co‐workers use in situ grazing‐incidence wide‐angle X‐ray scattering techniques to study the crystallization kinetics of 2D perovskites and reveal the role of additives in the crystallization process. The synergy between DMSO and KI additives can improve the crystal orientation and effectively passivate defects, owing to the sandwich‐type distribution of K +, delivering a high efficiency of 16.48%.